Integrating in vitro breeding, BLUP prediction, and marker analysis to enhance rice yield, quality, and blast resistance - Abdelkhalek, Samah M.; Abdelrahman, Mohamed; Mazal, Tahany M.; Kimiko, Itoh; Elshenawy, Mostafa; Aamer, Samah; Hassan, Amr A.; Attia, Kotb A.; Ammar, Megahed (Frontiers in Plant Science, 2025)
Rice is acting a critical role in global food security, being a staple food for more than half of the world’s population. In vitro-derived lines possess a significant opportunity to develop new plant material in a shorter time frame compared to conventional breeding. In the current study, we developed new rice genotypes via in vitro culture for enhanced yield, quality, and blast disease resistance. Significant differences were observed among the newly developed genotypes compared with the commercial cultivars for various vegetative and yield traits. The results indicated notable improved yield performance, quality, and blast resistance for the in vitro-developed lines. Furthermore, the selection of the top 5% of the genotypes resulted in a predicted genetic gain of 0.19 kg m-² for grain yield, representing a 20.88% improvement over the genotypes’ mean yield of 0.91 kg m-². Best linear unbiased prediction (BLUP) modeling for the studied traits was applied to identify the best-performing genotypes. Principal component analysis-based BLUP estimates identified two in vitro-derived lines, AC-2286 and AC-2729, as the best-performing in vitro genotypes. Both lines have higher yielding ability compared to the local cultivars; however, only AC-2286 was blast resistant under artificial inoculation and natural conditions. Interestingly, marker–trait association revealed that AC-2729 carries the favorable marker allele for grain yield, RM224-152bp, on chromosome 11 with a highly significant phenotypic effect (33%), while AC-2286 has more resistance ability to blast disease owing to its genetic background that carries several favorable blast-resistant alleles RM6887-152bp, RM224-165bp, RM13-151bp, and RM1370-165bp with high significant phenotypic effect (62%, 47%, 47%, and 31%, respectively). These findings increase the potential of the in vitro-derived lines for enhancing rice productivity, quality, and disease resistance in a few years compared to classic breeding, which provides valuable insights for future breeding programs.